Pattern Recognition, Hypotheses Generation, and Auditor Performance in an Analytical Task. - Bedard, Jean C.; Biggs, Stanley F. (The Accounting Review, 1991)
The article relates processes of pattern recognition and hypotheses generation to auditors' quality of performance in an analytical task. Professional standards for analytical procedures call for auditors to hypothesize likely causes of unexpected patterns in financial statement balances and to develop plans to investigate. Therefore, audit efficiency and effectiveness depend on competency in recognizing patterns in financial data and in hypothesizing likely causes of those patterns to serve as a guide for further testing. In the article, researchers conducted a laboratory study in which 21 auditors were asked to think aloud while performing an analytical procedures task. The case contained a seeded error that caused a fairly complex pattern of discrepancies between projected and unaudited financial ratios and balances. Think-aloud verbal protocols provided a trace of subjects' reasoning processes, and the seeded error provided an outcome criterion to evaluate the hypotheses they generated. This design supplies evidence needed to evaluate pattern recognition and hypothesis generation processes that lead to correct and incorrect outcomes.